Feminist Methodologies Experiments, Collaborations and Reflections - Harcourt, Wendy; van den Berg, Karijn; Dupuis, Constance; Gaybor, Jacqueline (Gender, Development and Social Change, 2022)
This open access book gives insights into feminist methodologies in theory and practice. By foregrounding the experiential and embodied nature of doing feminist research, this book offers valuable tools for feminist research as a continuous praxis. Emerging from a rich collective learning process, the collection offers in-depth reflections on how feminists shape research questions, understand positionality, share research results beyond academe and produce feminist intersectional knowledges. This book reveals how the authors navigate theory and practice, candidly exploring the difficulty of producing knowledge on the edge of academia and activism. From different points of view, places and disciplinary positions, artistic and creative experiments and collaborations, the book provides a multi-layered analysis. This book will be a valuable resource and asset to early career researchers and interdisciplinary feminist students who can learn more about the doing of feminist researchfrom realistic, accessible, and practical methodological tools and knowledge. Wendy Harcourt is Professor of Gender, Diversity and Sustainable Development at the International Institute of Social Studies of the Erasmus University Rotterdam. She is Coordinator of the WEGO-ITN "Well-being, Ecology, Gender and Community" - Innovation Training Network and Series Editor of the Palgrave series on Gender, Development and Social Change. She has written widely on gender and development, post-development, body politics and feminist political ecology. Karijn van den Berg is an independent feminist researcher who brings together environmental politics, feminism, activism and relations of power in her academic and political work, and strives to connect theory, practice and political organising.  Constance Dupuis is a researcher at the International Institute of Social Studies of the Erasmus University Rotterdam, funded by the WEGO-ITN "Well-being, Ecology, Gender and community" - Innovation Training Network. Her work focuses on ageing and intergenerational wellbeing from decolonial and feminist political ecology perspectives. Jacqueline Gaybor is a Senior Technical Advisor at Rutgers - a Dutch centre of expertise on sexual reproductive health and rights and she is a Lecturer at the Erasmus University College, of the Erasmus University Rotterdam. .